Validation of Cardiac Surgery Score (CASUS) in Postoperative Cardiac Patients. (December 2020) - Raut, Sarah; Hussain, Azar; Ariyaratnam, Priyadharshanan; Ananthasayanam, Ananthakrishnan; Vijayan, Ajith; Chaudhry, Mubarak; Loubani, Mahmoud
Introduction . Cardiac Surgery Score (CASUS) was introduced in 2005 as the first postoperative scoring system specific for patients who had cardiac surgery. Prior to this, European System for Cardiac Operative Risk Evaluation (EuroSCORE) has been used preoperatively, while Intensive Care National Audit and Research Centre Score (ICNARC) and Acute Physiology and Chronic Health Evaluation II (APACHE II) scores, which are widely used in general intensive care unit population, have been used to score cardiac patients postoperatively. The development of CASUS by Hekmat and colleagues for use in postoperative cardiac patients aims to change this. We wanted to validate CASUS against the well-established preoperative Logistic EuroSCORE, and postoperative APACHE II and ICNARC scores. Method . Institutional approval for this study was granted by the Audit and Clinical Governance Committee. We analyzed prospectively collected data of patients who had cardiac surgery in Castle Hill Hospital between January 2016 and September 2018. All patients who underwent surgery in the unit would have had Logistic EuroSCORE, APACHE, and ICNARC scores calculated as standard. CASUS was then calculated for these patients based on their day 1 postoperative variables. The scoring systems were compared and data presented as area under the receiver operating characteristic curve. Result. Our study shows that CASUS is the best predictor of mortality followed by ICNARC, Logistic EuroSCORE, and APACHE II. ICNARC score remains the most accurate predictor of renal and pulmonary complication followed by CASUS. Conclusion. CASUS is a useful scoring system in post-cardiac surgery patients. The accuracy of CASUS and ICNARC scores in predicting mortality, pulmonary, and renal complications are comparable.